AB0516 Early Lupus Project – A Multicentre Italian Study on Systemic Lupus Erythematosus of Recent Onset. (10th June 2014) - Prevete, I.; Sebastiani, G.; Piga, M.; Iuliano, A.; Bettio, S.; Bortoluzzi, A.; Coladonato, L.; Fineschi, I.; Spinelli, F.; Tani, C.; Mathieu, A.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is an autoimmune disease mostly affecting women during their thirties and forties. Objectives: Our objective is to prospectively collect the clinical and serological characteristics of an Italian population of SLE patients with a recent disease onset. In this first report we describe the characteristics obtained at study entry of the patients as yet enrolled, and make comparison with the parameters of activity and damage obtained after 12 months of follow-up. Methods: This is a multicentre prospective study. All patients with a diagnosis of SLE (1997 ACR criteria) and a disease duration lower than 12 months were consecutively enrolled in the study. The study started on 1st January 2012 and ended on 31st December 2013. Information on clinical and immunological characteristics at study entry and then every 6 months were collected into a specific electronic data base. Results: We enrolled 122 patients (102 F, 20 M), 94.3% whites, 5.7% of other ethnicity. Mean age (SD) of patients at study entry was 37.3 (14.3) years, mean age at disease onset (first symptom of SLE) was 34.8 (14.3), mean age at diagnosis was 36.9 (14.3) years. Mean disease duration (from diagnosis until study entry) was 2.9 (3.9) months. The frequency (from onset until enrollment) of the manifestations included in the classification criteria was: ANA 94.3%, immunologic disorders 85.2%, arthritis 61.8%, hematologic disorders 55.7%, malar rash 31.1%, photosensitivity 29.5%, serositis 27%, renal disorders 27%, oral ulcers 11.5%, neurologic disorders 8.2%, discoid rash 5.7%. The cumulative frequency of mucocutaneous symptoms was 77.8%. Autoantibody frequency (at enrollment) was: ANA 89.3%, anti-dsDNA 77.8%, anti-SSA 31.9%, anticardiolipin 24.5%, anti-nRNP 17.2%, anti-beta2GI 17.2, Lupus anticoagulant 16.3%, anti-SSB 13.11%, anti-Sm 12.3%. Eighty-three patients had at least a hospitalization in the period from diagnosis until study entry. The mean (SD) hospitalization number was 1.54 (1.58) for the whole cohort, and the mean number of days of hospitalization was 14.4 (14.5). Median (range) disease activity (ECLAM) was 4 (0-10), median damage (SLICC) was 0 (0-3), median patient's quality of life (VAS) was 53 (0-100). Fifty-nine patients completed 12 months of follow-up. Their ECLAM, SLICC and VAS were respectively 1 (0-4), 0 (0-4), 40 (0-100). Conclusions: In our cohort, only 31.1% of patients presented with the typical malar rash at the onset. On the contrary, a great proportion of patients presented with nonspecific symptoms, such as arthritis. This could delay the final diagnosis of SLE. Mean age at onset of in our patients was about 35 years; at the fulfillment of the ACR criteria, the mean age was about 37 years. Therefore, the mean time between the first manifestations and the final classification of SLE was 2 years. Disease activity showed improvement during a 12 months period, probably reflecting the relatively short time duration between diagnosis and enrollment. However, this study confirm that SLE is a severe disease even at onset, because most patients have a poor quality of life and the majority of them require at least a hospitalization since the beginning. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3347